Optimized TGA-based experimental method for studying intrinsic kinetics of coal char oxidation under moderate or intense low-oxygen dilution oxy-fuel conditions. (15th February 2023) - Hu, Fan; Xiong, Biao; Liu, Xuhui; Huang, Xiaohong; Li, Yu; Liu, Zhaohui
Abstract: Accurate assessment of coal char oxidation kinetics is essential for the design of efficient combustion systems; nonetheless currently, there is little research on this aspect under moderate or intense low-oxygen dilution (MILD) oxy-fuel (MO) conditions. In this study, experimental and modeling studies were conducted for analyzing the intrinsic kinetic properties of coal char oxidation under MILD air-combustion (MA) and MO conditions based on thermogravimetric analysis (TGA). The experimental conditions were improved to minimize various diffusion resistances in the crucible during the TGA experiments. Under the optimal conditions of TGA experiments, the reactivity differences of coal char under the MA and MO atmospheres were small. Both nonlinear model-fitting and linear model-free analysis methods were used to analyze kinetic parameters of coal char oxidation. The results showed that the random pore model correlated the best with the experimental results. The activation energies of coal char under the optimal conditions in MA and MO atmospheres (i.e., 104.4 kJ/mol and 98.2 kJ/mol, respectively) were much higher than those obtained by the conventional method. The reaction orders of coal char oxidation in MA and MO atmospheres were close to 1.0, and the specific values were affected by the diffusion effect and background atmosphere. Graphical abstract: Image 1 Highlights: TGA experimental method is optimized by minimizing various diffusion resistances. Kinetics of coal char in MA and MO atmospheres have been studied by the new method. Kinetic parameters obtained by the new method exhibit obvious improvements.